The Influence of Leadership Style Organizational Culture and Rewards for Motivation Work and Teacher Performance in Formal Education Units - Ima Wijayanti Safitri; Sukmo Hadi Nugroho (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The contribution of this study can provide new knowledge at the theory or scientific level of human resource management and add new references and management implications that can be positively applied to non-profit organizations. Based on the results of previous studies and empirical theories related to human resource management, this study was conducted using methods of data collection of questionnaires by distributing questionnaires on the Internet, the selection of respondents was based on the purposive sampling method of teachers of primary education units of DKI Jakarta 1 up to 155 teachers. The administrative effect of this research on organizations is that it is possible to stimulate the role of managers to be able to increase the motivational work of teachers to offer positive changes to the motivational work to achieve the goals of the organization.